El "mundo feliz" del liberalismo. - Francisco, Andrés de (Cuadernos de Relaciones Laborales, 2000)
In this article, the b~ ~wht could be considered te dogmas of economíci `Tirstly, te article exami Profesor de la Uni' * Andrév de Francisco El «mundo feliz» del liberalismo nes hte beliefin self-regulation of relations and trade based on decentralized decision-making processes. Several notions of equilibrium are considered in this anaiysis as weB as the various models of trade and selfregulation and adjustment mechanisms. Finally, the article considers what are known as explanations of the invisible hand, the evolutionary paradigm as compared to te views espoused by naturalist determinism and constructivist rationalism Liberalism's second dogma is that market equilibrium is good equilibrium regardless of equity in distribution aud social integration. In this dogma, efflciency stads as te ethical and regulatory criterion in socia choice.
Keywords: liberalism; economic; self-regulation; invisible hand; paradigm; evolutionary; economic efficiency; equity in distribution; social